2022
DOI: 10.1111/jcmm.17294
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline protects human retinal pigment epithelium from hydrogen peroxide and iron/ascorbate induced damages

Abstract: Oxidative stress appears to play an important role during ageing of the retina and in the pathophysiology of retinal diseases, such as age-related macular degeneration (ARMD). [1][2][3] The retinal pigment epithelium (RPE), localized between the choroid and the neural retina, is particularly vulnerable to oxidative damage caused by reactive oxygen species (ROS). 4 Hydrogen peroxide (H 2 O 2 ) is a ROS generated during RPE phagocytosis of photoreceptor outer segments 5,6 and during light irradiation of melanin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…Our results showed that citrulline prevented the IH-increase in O 2 − and XOX activity and also decreased infarct size without any modification in the eNOS activity and expression ( Figure S3c,d ). This is in agreement with other studies highlighting the potential anti-oxidant effects of citrulline: an increase in SOD activity and a decrease in lipid peroxidation in the heart tissue in a rat model of sepsis [ 66 ]; a blunt in H 2 O 2 − induced ROS production in retinal epithelial cells while limiting lipid peroxidation and preventing cell death [ 67 ]; a renal decrease in oxidative-DNA damage without affecting the eNOS expression in spontaneously hypertensive rats [ 35 ]. This suggests that citrulline can preserve the heart against oxidative stress without any modification of the eNOS expression.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that citrulline prevented the IH-increase in O 2 − and XOX activity and also decreased infarct size without any modification in the eNOS activity and expression ( Figure S3c,d ). This is in agreement with other studies highlighting the potential anti-oxidant effects of citrulline: an increase in SOD activity and a decrease in lipid peroxidation in the heart tissue in a rat model of sepsis [ 66 ]; a blunt in H 2 O 2 − induced ROS production in retinal epithelial cells while limiting lipid peroxidation and preventing cell death [ 67 ]; a renal decrease in oxidative-DNA damage without affecting the eNOS expression in spontaneously hypertensive rats [ 35 ]. This suggests that citrulline can preserve the heart against oxidative stress without any modification of the eNOS expression.…”
Section: Discussionsupporting
confidence: 92%